1998
DOI: 10.1021/bi981269m
|View full text |Cite
|
Sign up to set email alerts
|

A Buried Polar Interaction Can Direct the Relative Orientation of Helices in a Coiled Coil

Abstract: Coiled coils consist of bundles of two or more alpha-helices that are aligned in a parallel or an antiparallel relative orientation. The designed peptides, Acid-p1 and Base-p1, associate in solution to form a parallel, heterodimeric two-stranded coiled coil [O'Shea, E. K., Lumb, K. J., and Kim, P. S. (1993) Curr. Biol. 3, 658]. The buried interface of this complex is formed by hydrophobic Leu residues, with the exception of an Asn residue from each strand that is positioned to engage in a buried polar interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
192
1
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(202 citation statements)
references
References 40 publications
5
192
1
4
Order By: Relevance
“…These a and d positions are oriented on one side of an alpha helix and, by interacting with the a and d residues of a second alpha helix, form a hydrophobic core that stabilizes the coiled coil. In experiments performed with synthetic coiled coils, introduction of a single polar amino acid within the hydrophobic core can be tolerated and, in fact, influences the orientation assumed by the coiled coil (15,24). We reasoned that introduction of Cys residues within the hydrophobic core of the delta antigen coiled coil may similarly be tolerated, and therefore we individually substituted Cys residues at all a and d positions throughout the delta antigen coiled coil.…”
Section: Resultsmentioning
confidence: 99%
“…These a and d positions are oriented on one side of an alpha helix and, by interacting with the a and d residues of a second alpha helix, form a hydrophobic core that stabilizes the coiled coil. In experiments performed with synthetic coiled coils, introduction of a single polar amino acid within the hydrophobic core can be tolerated and, in fact, influences the orientation assumed by the coiled coil (15,24). We reasoned that introduction of Cys residues within the hydrophobic core of the delta antigen coiled coil may similarly be tolerated, and therefore we individually substituted Cys residues at all a and d positions throughout the delta antigen coiled coil.…”
Section: Resultsmentioning
confidence: 99%
“…The ground-breaking work of DeGrado and coworkers (17)(18)(19)(20) has led to the development of well packed helix bundle proteins with natural-like sequences and stabilizing interactions. In their work, and pioneering work from other laboratories, a specific fold has been achieved via the formation of tertiary hydrogen bonds (20)(21)(22)(23), crystal contacts (18,24), disulfide bonds (25,26) or favorable charge-charge interactions (19,20,23,24,26,27). Previous work toward simplifying proteins has shown that a native-like Src homology 3 fold can be achieved with chiefly five different residues (although 13 in total) (28), and a four-helix bundle protein can be formed from only nine different residues (29).…”
Section: The Presence Of An Aromatic Ring At the C Terminus Is Requirmentioning
confidence: 99%
“…The hydrophobic effect drives the burial of nonpolar residues at the helix-pairing interface and influences geometric details of resulting structures (4). Electrostatic and polar residues at buried or solvent-exposed locations provide additional means to manipulate structural features by stabilization or destabilization (negative design) of key interactions (5)(6)(7)(8).…”
mentioning
confidence: 99%